REGULATORY MONITORING AND REGULATEE’S FIRM PERFORMANCE: AUDIT THEMATIC FINDING ON WATER OPERATOR PERFORMANCE IN MALAYSIAN WATER SERVICES INDUSTRY - Ir. Muhamad Sobri Bin Zakaria; Haslina Binti Hassan; Prof. Madya Dr Mohd Hizam bin Hanafiah, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
This study provides a report of the audit thematic findings on the regulatory role towards regulatee’s firm performance. Based on the literature, audit activities is part of monitoring mechanism that can improve firm performance in the situation where a controlling power such as holding shares and executive power does exist. However, in the context of regulator and regulatee relationship in Malaysian water services industry, the regulator has an authority to control and monitor the regulatee’s firm performance. The regulator has monitoring power stipulated by law, Water Services Industry Act 2006 (Act 655). In this scenario, the regulator does not hold any share in the regulatee’s firm, neither hold executive power such as sitting as board of directors. Method: Conducting longitudinal thematic audit on water services providers (Regulatee /Auditee) and continuous monitoring activities. Sixteen study with five themes on thirteen water operators in Malaysia have been conducted to confirm on the finding. The audit execution holds by Water Industry Audit Division (Auditor), a regulator representative. Result: Consistent with the prior study and in line with the objective of the regulator establishment in ensuring the sustainability of water services industry, the report found several improvements in regulatee’s firm performance that further improves national water services efficiency. Conclusion: This study extent the current dimension of a common auditor’s role to regulatory audit activities as a monitoring mechanism that elaborates regulatory effectiveness towards regulatee’s firm performance.